Ultrasonographic evaluation of intramandibular ameloblastoma - Elio Hitoshi Shinohara; Shajadi Carlos Pardo Kaba; Marcelo Zillo Martini; Carlos Henrique Hueb (Indian Journal of Dental Research, 2013)
Ultrasonography (US) is the diagnostic tool of choice for evaluating soft tissue lesions in the head and neck region. It is an economic, noninvasive, easily performed exam and provides real-time images, without the exposure to ionizing radiation, and contrast media is not required. It is usually believed that bone tissue constitutes an obstacle for its utilization, due to the reflection of sonographic waves. A case of mandibular intraosseous cystic pathology is reported, with utilization of US for evaluating the content of the lesion and planning the surgical procedure.